Some numerical radius inequalities for d-tuples of operators - Messaoud Guesba; Ould Ahmed Mahmoud Sid Ahmed (Surveys in Mathematics and its Applications)
Our aim in this paper is to give new numerical radius inequalities for d-tuples of operators on a complex Hilbert space. We prove several inequalities for multivarible operators on a complex Hilbert space. Based on that some numerical radius inequalities due to Dragomir for a single operator.